The Influence of Self-Efficacy on The Resiliency of Communities Working in Non-Star Accommodation Business in Ubud Village Post-Pandemics Covid-19 - I Putu Andre Adi Putra Pratama; I Gusti Putu Bagus Sasrawan Mananda; Ni Putu Ratna Sari (Journal of Social Research, 2023)
The Covid-19 pandemic crisis is one of the catastrophic events that has caused economic changes and make an impact on communities psychological who work in non-star accommodations in Ubud Village. This study aims to analyze the effect of self-efficacy on communities resilience who work in non-star accommodations in Ubud Village, Gianyar, Bali, post-pandemics Covid-19. This study uses a sequential explanatory mixed method by combining quantitative and qualitative research approaches. The total of samples taken in this study was 100 respondents determining the sample using a proportionate stratified random sampling from the local community of Ubud, ethnically Balinese workers in non-star accommodation businesses in Ubud Village such as homestays, bungalows, villas, and guest houses then the data were analyzed using Structural Equation Modeling (SEM) with the help of Smart-PLS for student software. The results showed that the hypothesis in this study was accepted, and showed that self-efficacy had a significant and positive effect on resilience. The results of this study indicate that resilience can be realized through the role of self-efficacy as confidence in self-competence so that the community who works in the non-star accommodation business in Ubud Village can develop a resilient personality after the Covid-19 pandemic.